2012
DOI: 10.1002/ppap.201100137
|View full text |Cite
|
Sign up to set email alerts
|

Amino‐rich Plasma Polymer Films Prepared by RF Magnetron Sputtering

Abstract: Radio frequency magnetron sputtering of nylon 6.6 followed by N2/H2 plasma post‐treatment was used for deposition of nitrogen‐rich film with amino functionalities on the surface. The maximal NH2/C concentration obtained was 11% and the NH2/N reached 13.5%. The films are positively charged with an isoelectric point of 4.5. The interaction between the film and the buffer solution was studied and shows that the films are stable in cell culture conditions. A quartz crystal microbalance study showed the ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Surface plasma modification is an excellent approach to modify the chemical structure 26 and produce the targeted nitrogen functionality 27 28 29 . It has been demonstrated that a nitrogen plasma-modified surface can serve as a powerful artificial microenvironment to regulate osteogenic differentiation of osteoblasts 30 31 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface plasma modification is an excellent approach to modify the chemical structure 26 and produce the targeted nitrogen functionality 27 28 29 . It has been demonstrated that a nitrogen plasma-modified surface can serve as a powerful artificial microenvironment to regulate osteogenic differentiation of osteoblasts 30 31 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Tertiary amines are produced selectively on the PE in spite of the existence of N-C = O groups due to oxidation. It can be inferred that on the pyrolytic carbon structure, other nitrogen functionalities (for example, -NH 2 ) can be generated by increasing the hydrogen amount in the implanted ions 27 . In addition, most of the C = C bonds remain on PArN implying that the π-conjugated structures are abundant on the PArN surface.…”
Section: Resultsmentioning
confidence: 99%
“…The functionalized NCD samples were placed on top of the glass bead layer to avoid direct contact between the sample surface and TFBA liquid. The plastic container was then sealed and placed into an oven at 45° C for 2 h. After the derivatization, the fluorine concentration was determined by XPS and the primary amine [NH 2 ] concentration was calculated as it is described in: NnormalH2=F/3C(8F/3)×100% where F and C are the fluorine and carbon concentrations, respectively, after the reaction with TFBA. The term F/3 then indicates the amount of primary amines, the term 8F/3 corresponds to the amount of carbon atoms added by TFBA molecules themselves and the term C − 8F/3 is the original carbon concentration on the surface …”
Section: Methodsmentioning
confidence: 99%
“…The present work provides the first chemical analysis of tholins thin films along their depth profile, using XPS (X-ray Photoemission Spectroscopy) -3 -and SIMS (Secondary Ion Mass Spectrometry) analysis. Those two techniques are commonly used for organic films analysis in general, [22][23][24][25] and are well adapted for nitrogen containing films in particular [26][27][28]. Moreover two kinds of substrates are used, made of CaF 2 and SiO 2 , to analyze the sensitivity of the solid deposition to the nature of the substrate.…”
Section: Introductionmentioning
confidence: 99%